1985
DOI: 10.1016/0196-9781(85)90331-6
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic distribution of 125I calcitonin gene-related peptide binding sites in the rat central nervous system

Abstract: SKOFITSCH, G. AND D. M. JACOBOWITZ. Autoradiographic distribution of v'-:'l calcitonin gene-related peptide binding sites in the rat central nervous system. PEPTIDES 6(5) [975][976][977][978][979][980][981][982][983][984][985][986] 1985.--Using autoradiographic method and "-':'I-Tyr ° rat CGRP as a ligand, receptor binding sites were demonstrated in the rat central nervous system. Saturation studies and Scatchard analysis of CGRP-binding to slide mounted tissue sections containing primarily cerebellum showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
2

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(34 citation statements)
references
References 33 publications
3
29
2
Order By: Relevance
“…The distribution of CGRP terminal fields is in relatively good agreement with the distribution of CGRP binding sites in the rat forebrain (Skofitsch and Jacobowitz, 1985a;Inagaki et al, 1986;Sexton et al, 1986;Kruger et al, 1988a;van Rossum et al, 1997). In the forebrain, discrepancy is found only in the nucleus accumbens and in the basolateral amygdaloid nucleus where CGRP binding sites are abundant, but CGRP terminals are scarce.…”
Section: Bsupporting
confidence: 63%
“…The distribution of CGRP terminal fields is in relatively good agreement with the distribution of CGRP binding sites in the rat forebrain (Skofitsch and Jacobowitz, 1985a;Inagaki et al, 1986;Sexton et al, 1986;Kruger et al, 1988a;van Rossum et al, 1997). In the forebrain, discrepancy is found only in the nucleus accumbens and in the basolateral amygdaloid nucleus where CGRP binding sites are abundant, but CGRP terminals are scarce.…”
Section: Bsupporting
confidence: 63%
“…Because peptides often act for long periods of time, as we have found from local BNST infusions of either CRF (Liang et al, 1992) or CGRP (Sink et al, 2011), we believe that accelerated development of small molecule ligands for these receptors, and their evaluation in anxiety models such as the one used here, may be a prudent strategy for the development of new anxiolytic compounds with novel mechanisms of action. We have found, for example, that oral administration of the non-peptide CRF-R1 antagonist GSK876008 disrupts sustained, but not phasic startle increases to conditioned fear stimuli (Walker et al, 2009a, b), and also startle increases evoked directly by calcitonin gene-related peptide (CGRP) infusions into the BNST (Sink et al (2011) and unpublished observations), where receptors for both peptides are abundant (Skofitsch and Jacobowitz, 1985;Kruger et al, 1988;Chalmers et al, 1995;Christopoulos et al, 1995). We have also found that intra-BNST CGRP infusions increase anxiety measures in the plus maze, and that intra-BNST infusions of a CGRP antagonist decrease sustained startle increases produced by the predator odor 2,5-dihydro-2,4,5-trimethylthiazoline (Sink et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that CGRP receptor populations are highly localized to discrete discontiguous areas very much limits the number of possible alternatives. Based on proximity, the most likely alternative (i.e., to the BNST) would be that CGRP 8 -37 was acting on receptors just ventral and lateral to the BNST as this area also contains significant numbers of CGRP receptors (Skofitsch and Jacobowitz 1985;Kruger et al 1988;Christopoulos et al 1995). This population is continuous with that found in the BNST and, as such, it would be difficult to compare these alternatives by evaluating the effect of infusions into the two areas (i.e., it is likely that we are blocking some of these receptors with intra-BNST infusions, and equally likely that infusions into this alternative area would influence BNST CGRP receptors).…”
Section: Discussionmentioning
confidence: 99%